The Workshop on Physics at the First Muon Collider and at the Front End of a Muon Collider 1998
DOI: 10.1063/1.56245
|View full text |Cite
|
Sign up to set email alerts
|

A small target neutrino deep-inelastic scattering experiment at the first muon collider

Abstract: Abstract. Several di erent scenarios for neutrino scattering experiments using a neutrino beam from the muon collider complex are discussed. The physics reach of a neutrino experiment at the front end of a muon collider is shown to extend far beyond that of current neutrino experiments, since the high intensity neutrino beams one would see at the muon collider allow for a large exibility in choosing neutrino targets. Measurements of quark spin, A-dependence of the structure function xF 3 and neutral current c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Raw event rates in such a polarized target could be of order 10 8 events per year, as shown in Table 2. A previous study for νMCs [42] has shown that a 200 kg target of polarized butanol with 10% polarization could measure the strange sea polarization to about 3% in a one year run in a beam downstream of a 250 GeV muon collider with a 10 m straight section.…”
Section: Experimental Setup and Measurement Techniquementioning
confidence: 99%
“…Raw event rates in such a polarized target could be of order 10 8 events per year, as shown in Table 2. A previous study for νMCs [42] has shown that a 200 kg target of polarized butanol with 10% polarization could measure the strange sea polarization to about 3% in a one year run in a beam downstream of a 250 GeV muon collider with a 10 m straight section.…”
Section: Experimental Setup and Measurement Techniquementioning
confidence: 99%
“…This detector would be able to tag the production of charmed particles by observing high momentum final state leptons, and with a sufficiently fine-grained 2) For example, the measurements of α S [4] and sin 2 θ W [5] in the CCFR experiment upstream tracker, charmed final state particles could be tagged via detached vertices [6]. Physics goals of an experiment using this detector are described elsewhere in these proceedings [1].…”
Section: Conventional Fixed-target Geometrymentioning
confidence: 99%
“…upstream tracker, charmed final state particles could be tagged via detached vertices [6]. Physics goals of an experiment using this detector are described elsewhere in these proceedings [1].…”
Section: Conventional Fixed-target Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The gigantic flux of neutrinos from a millimole of stored muons means that the familiar massive neutrino detectors would be inappropriate devices [35]. Thin targets, instead of extremely massive target calorimeters, become the order of the day.…”
Section: Neutrino Beams From Stored Muonsmentioning
confidence: 99%